Library associations: making connections to enable effective change (Journal of EAHIL, 2022)
Decisions by library associations impact on everyone involved in library and information services. The committee of the Library Association of Ireland, Health Sciences Libraries Group conducted an online survey about association and group membership. Our (49) responses and literature review provide a useful guide to what is wanted and needed. We learned about the value of taking a holistic, connected approach to enhancing expertise through continuing professional development, progressing the interests of our profession, and supporting collegiality and knowledge exchange by uniting us as a community. Our findings show the importance of belonging to a professional group that not only provides comprehensive tangible supports but also facilitates a network of stakeholders with whom we can engage, share and collaborate.